PERFORMANCE MOTOR-GENERATOR OPERATED WITH OTTO CYCLE GASOLINE AND BIOGAS FROM THE PIG. - Rossetto, C.; Melegari De Souza, S. N.; Klaus, O. L. (Revista Brasileira de Engenharia de Biossistemas, 2014)
The search for new energy sources that do not pollute the environment and mitigating the environmental impacts generated by population increase, opens a new perspective in the research field of biogas from the sewage treatment outcome. The process of transformation of energy generated by the combustion of biogas energy in Otto engines and subsequent transformation into electrical energy cycle is easy to perform some adjustments to the engine, this work was being performed only necessary to replace the carburetor by a mixer / air Venturi-type fuel. The objective of this study was to evaluate the performance of Otto cycle engine-generator powered with biogas from swine. As control assays with gasoline were used, simulating different working conditions, with loads of 0; 0,250 kW (10% load); 0.500 kW (20% load); 0.750 kW (30% load); 1 kW (40% load); 1,250 kW (50% load); 1,500 kW (60% load); 1,750 kW (70% load); 2 kW (80% load); 2.250 kW (90% load) and 2,500 kW (100% load). Where emissions of carbon dioxide (CO2), carbon monoxide (CO) and nitrogen oxide (NOx) were evaluated and analyzed the performance of motor-generator that was down around 76% less when compared to gasoline, and necessary adjustments for better performance